Antibiotic Resistance and Toxin Production of Clostridium difficile Isolates from the Hospitalized Patients in a Large Hospital in Florida - Peng, Zhong; Addisu, Anteneh; Alrabaa, Sally; Sun, Xingmin (Frontiers in Microbiology, 2017)
Clostridium difficile is an important cause of nosocomial acquired antibiotic-associated diarrhea causing an estimated 453,000 cases with 29,000 deaths yearly in the U.S. Both antibiotic resistance and toxin expression of C. difficile correlate with the severity of C. difficile infection (CDI). In this report, a total of 139 C. difficile isolates from patients diagnosed with CDI in Tampa General Hospital (Florida) in 2016 were studied for antibiotic resistance profiles of 12 types of antibiotics and toxin production. Antibiotic resistance determined by broth microdilution method showed that strains resistant to multi-antibiotics are common. Six strains (4.32%) showed resistance to 6 types of antibiotics. Twenty strains (14.39%) showed resistance to 5 types of antibiotics. Seventeen strains (12.24%) showed resistance to 4 types of antibiotics. Thirty-nine strains (28.06%) showed resistance to 3 types of antibiotic. Thirty-four strains (24.46%) showed resistance to 2 types of antibiotics. While, all isolates were susceptible to metronidazole, and rifaximin, we found that one isolate (0.72%) displayed resistance to vancomycin (MIC ≥ 8 µg/ml), and another one was resistant to fidaxomicin (MIC >1 µg/ml). The percentage of isolates resistant to cefoxitin, ceftriaxone, chloramphenicol, ampicillin, clindamycin, erythromycin, gatifloxacin, and moxifloxacin was 75.54%, 10.79%, 5.76%, 67.63%, 82.70%, 45.32%, 28.06%, and 28.78%, respectively. Toxin profiling by PCR showed the isolates include 101 (72.66%) A+B+CDT- strains, 23 (16.55%) A+B+CDT+ strains, 3 (2.16%) A-B+CDT+ strains, 1 (0.72%) A-B+CDT- strains, and 11 (7.91%) A-B-CDT- strains. Toxin production determined by ELISA using supernatants of bacterial culture harvested at 12, 24, 48, and 72 hours of post inoculation (hpi) showed that the toxins were mainly produced between 48 hpi and 72 hpi, and toxin B (TcdB) was produced faster than toxin A (TcdA) during the experimental time (72 hpi). In addition, the binary-positive strains were likely to yield more toxins compared to the binary-negative strains. This work contributes to the current understanding of the antibiotic resistance and virulence of C. difficile clinical strains.